Preoperative assessment of retrorectal tumours. (13th March 2014) - Sagar, A J; Koshy, A; Hyland, R; Rotimi, O; Sagar, P M
Abstract: Background: Retrorectal tumours present diagnostic and surgical challenges. This study aimed to identify whether preoperative imaging and/or biopsy provide diagnostic accuracy. Methods: A consecutive series of patients who had undergone excision of a retrorectal tumour were identified from a database (2002–2013). Details of patient demographics, preoperative presentation, imaging, biopsy, surgical procedure, and gross and microscopic pathology were reviewed. Preoperative imaging and/or biopsies were compared with eventual pathology findings. Results: In total, 76 patients were identified, all of whom had undergone preoperative cross-sectional imaging whereas only 22 had preoperative biopsy. Imaging correctly discriminated benign from malignant tumours in 72 of the 76 patients (specificity 97 per cent, sensitivity 88 per cent, positive predictive value 88 per cent and negative predictive value 97 per cent). The corresponding values for preoperative biopsy (benign versus malignant) were 100, 83, 100 and 93 per cent. None of the four patients who were assessed incorrectly as having benign or malignant disease on imaging would have undergone an alternative procedure had this been known before surgery. Preoperative biopsy did not significantly influence patient management, and the absence of preoperative biopsy had no detrimental effect; a definitive preoperative histological diagnosis would not have influenced subsequent management. Conclusion: Preoperative imaging was accurate in the assessment of retrorectal tumours, whereas biopsy did not add to the surgical strategy. Abstract : Biopsy may not be warranted